Effect Of Selected Non-Starch Polysaccharides And Bulk Sweeteners On The Properties Of Acid-Thinned Starch Jelly Candy - Chapakiya, Habilla (2012)
Jelly candy samples based on acid thinned starch were developed. The effects of selected anionic non-starch polysaccharides (NSP: pectin, carboxymethyl cellulose, and alginates), and low-calorie bulk sweeteners (isomalt, maltitol and isomaltulose) on the physical properties of starch-based jelly candy were studied for selected properties such as pasting properties, viscoelasticity, flow properties, textural properties, storage stability, sensory properties, and glycemic index. Addition of the selected NSP was found to significantly increased peak viscosity of starch paste and this suggests that NSP added may increase viscous load during cooking of acid thinned starch slurry, especially when alginates and carboxymethyl cellulose were added.